Unravelling the ketone story. Secondary vessel use at the Ness of Brodgar, Orkney, Scotland - Julia Becher; Alexandre Lucquin; Rowan McLaughlin; Martine Regert; Mark Edmonds; Jan Blatchford; Nick Card; Anne Mitchell; Helen M. Talbot; Roy Towers; Oliver E. Craig (Organic Geochemistry, 2026)

Combination with a FtsZ inhibitor potentiates the in vivo efficacy of oxacillin against methicillin-resistant Staphylococcus aureus - Malvika Kaul; Edgar Ferrer-González; Lilly Mark; Ajit K. Parhi; Edmond J. LaVoie; Daniel S. Pilch (Medicinal Chemistry Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Intrusion errors moderate the relationship between blood glucose and regional cerebral blood flow in cognitively unimpaired older adults - Kelsey R. Thomas; Alexandra J. Weigand; Isabel H. Cota; Emily C. Edmonds; Christina E. Wierenga; Mark W. Bondi; Katherine J. Bangen (Brain Imaging and Behavior, 2022)
Regional cerebral blood flow (CBF) has a complex relationship with cognitive functioning such that cognitively unimpaired individuals at risk for Alzheimer’s disease (AD) may show regional hyperperfusion, while those with cognitive impairment typically show hypoperfusion. Diabetes and word-list intrusion errors are both linked to greater risk of cognitive decline and dementia. Our study examined associations between fasting blood glucose, word-list intrusion errors, and regional CBF. 113 cognitively unimpaired older adults had arterial spin labeling MRI to measure CBF in a priori AD vulnerable regions: medial temporal lobe (MTL), inferior parietal lobe (IPL), precuneus, medial orbitofrontal cortex (mOFC), and pericalcarine (control region). Hierarchical linear regressions, adjusting for demographics, vascular risk, and reference CBF region, examined the main effect of blood glucose on regional CBF as well as whether intrusions moderated this relationship. Higher glucose was associated with higher CBF in the precuneus (β = .134, 95% CI = .007 to .261, p = .039), IPL (β = .173, 95% CI = .072 to .276, p = .001), and mOFC (β = .182, 95% CI = .047 to .320, p = .009). There was no main effect of intrusions on CBF across regions. However, the glucose x intrusions interaction was significant such that having higher glucose levels and more intrusion errors was associated with reduced CBF in the MTL (β = -.186, 95% CI = -.334 to -.040, p = .013) and precuneus (β = -.146, 95% CI = -.273 to -.022, p = .022). These findings may reflect early neurovascular dysregulation, whereby higher CBF is needed to maintain unimpaired cognition in individuals with higher glucose levels. However, lower regional CBF in unimpaired participants with both higher glucose and more intrusions suggests a failure in this early compensatory mechanism that may signal a decrease in neural activity in AD vulnerable regions.

The diversity of arbuscular mycorrhizas of selected Australian Fabaceae - Mark Tibbett; Megan H. Ryan; Susan J. Barker; Yinglong Chen; Matthew D. Denton; Tamara Edmonds-Tibbett; Christopher Walker (Plant Biosystems, 2008)

Inhabiting neolithic landscapes - Mark Edmonds (Journal of Quaternary Science, 1999)